A 3D approximate hybrid algorithm for stope boundary optimization. (March 2020) - Nikbin, V.; Ataee-pour, M.; Shahriar, K.; Pourrahimian, Y.
Abstract: Determining stope boundaries is one of the critical steps to be taken when an underground mining method is selected; because of their significant impact on the profitability of the mining project, the stope boundaries have to be optimum to achieve maximum profits. This paper introduces a new hybrid algorithm that is a combination of dynamic programming and greedy algorithm. Although this proposed algorithm may fail to provide a true optimum solution, it generates better solutions than existing algorithms do. The new proposed algorithm and three existing algorithms are used to find the optimal stope boundaries on a real case ore body. The results demonstrate that the proposed algorithm can improve the profit by 117.78%, 16.86% and 0.42% compared to Floating Stope, Maximum Value Neighborhood (MVN), and Greedy algorithm solutions, respectively, on a real case study at a reasonable CPU time.